Mixed-Integer Nonlinear Programming Approach for Short-Term Hydro Scheduling - Catalao, J P S; Pousinho, H M I; Mendes, V M F (Revista IEEE América Latina, 2010)
This paper is on the problem of short-term hydro scheduling, particularly concerning a head-sensitive hydro chain. A novel mixed-integer nonlinear programming approach is proposed for optimizing power generation efficiency. The proposed approach considers not only the nonlinear dependence between power generation, water discharge and head, but also start-up costs for the hydro units and discontinuous operating regions, in order to obtain more realistic and feasible results. Numerical results based on one of the main Portuguese cascaded hydro systems illustrate the proficiency of the proposed approach.